Role of Intracellular Signaling Events in ADP-induced Platelet Aggregation - Daniel, James L.; Dangelmaier, Carol; Jin, Jianguo; Kim, Young B.; Kunapuli, Satya P. (Thrombosis and Haemostasis, 1999)
Human platelets express two distinct G protein-coupled ADP receptors, one coupled to phospholipase C through Gq, P2Y1, and the other to inhibition of adenylyl cyclase through Gi, P2TAC. We have recently shown that concomitant intracellular signaling from both the P2TAC and P2Y1 receptors is essential for ADP-induced platelet aggregation. Previous studies have tested whether ADP causes a decrease in the basal cAMP level and this reduction promotes platelet aggregation, but did not study the effect of decreased cAMP levels when the Gq pathway is selectively activated. Since we are now aware that platelet aggregation requires activation of two receptors, we investigated whether the function of P2TAC receptor activation, leading to inhibition of platelet adenylyl cyclase, could be replaced by direct inhibition of adenylyl cyclase, when Gq pathway is also activated, a possibility that has not been addressed to date. In the present study, we supplemented the P2Y1 mediated Gq signaling pathway with inhibition of the platelet adenylyl cyclase by using SQ22536 or dideoxyadenosine, or by selective activation of the α2A adrenoceptors with epinephrine. Although SQ22536, dideoxyadenosine, and epinephrine reduced the cAMP levels, only epinephrine could mimic the P2TAC receptor mediated signaling events, suggesting that reduction in basal cAMP levels does not directly contribute to ADP-induced platelet activation. Adenosine-5’-phosphate-3’-phosphosulfate, a P2Y1 receptor antagonist, completely blocked ADP-induced inositol 1,4,5-trisphosphate and inositol 1,3,4-trisphosphate formation suggesting that P2TAC-mediated activation of Gi (or other G proteins) does not activate phospholipase C. These results suggest that a signaling event downstream from Gi, independent of the inhibition of platelet adenylyl cyclase, contributes to αIIbβ3 activation.